Corporate income tax, IP boxes and the location of R&D - Pranvera Shehaj; Alfons J. Weichenrieder (International Tax and Public Finance, 2024)
We discuss corporate tax effects on multinationals' R&D. Theoretically, we find that a host country's tax increase may boost local R&D expenditure: while R&D becomes deductible at a higher rate, this higher rate may not apply to all R&D returns. First, as R&D creates a public good within the MNE, some R&D returns are taxed at other countries' tax rates. Second, some of the R&D returns are taxed at a lower IP regime tax rate. The positive tax rate effect is empirically supported by country-by-country R&D data of U.S.-owned subsidiaries for countries that have an IP regime.
Keywords: H25; H26; O3; 340; Corporate income tax; R&D; Intellectual property regimes; Patent box; International profit shifting